The Effectiveness of Eclectic Method in Teaching Writing English of Recount Text for the Eight Grade Students of SMPN 1 Keruak - Lalu Suparman (LP2M STIT Palapa Nusantara, 2017)
The aim of the study was to examine the effectiveness of eclectic method to improve students’ writing skill at the eighth grade students of SMP Negeri 1 Keruak, focusing on (1) Is eclectic method effective in writing skill at the eighth grade students of SMP Negeri 1 Keruak in the academic year 2016-2017? and (2) How is the effectiveness of the eclectic method to improve students’ writing skill at the eighth grade students of SMP Negeri 1 Keruak in the academic year 2016-2017?. The design of this research was a pre-experimental pre-test and post-test research. It means this research only applied the eclectic method to the experimental group that consisted of 36 students. The sample of the study was taken by using cluster random sampling technique. In gaining pre-test and post-test data, the students required to do the individual task in writing the monolog text of recount based on the material that was learnt before. Then the pretest and post-test data was analyzed by using descriptive statistics and Paired Sample t-test to test the hypothesis. Having collected and calculated the data by using descriptive statistics, it was found out that descriptive statistic results showed that the mean score of the pre-test was 7.21 while the mean of the post-test was 9.25. The result of hypothesis testing by using Paired-Sample t-test was t(27) = 11.68 at p = .000. It was lower than .05 so it means that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. In other word that the use of eclectic method was significantly effective in writing skill to the eighth grade students of SMP Negeri 1 Keruak in the academic year 2016-2017.